PENGARUH MINAT DAN MOTIVASI TERHADAP PRESTASI BELAJAR SISWA-SISWI SDN BINTARA VII KOTA BEKASI - Mardiah, Enok (JMIE (Journal of Madrasah Ibtidaiyah Education), 2019)
The goal of this research to see affect of interesting and motivation toward the students learning achievement at VII Bintara elementary school. Bekasi city. The research using description approach and quantitative method with correlation design. The result of this research show learning that both free variables learning interesting (X1) and learning motivation (X2) have a strong affect and significant toward the bound variables learning achievement (Y) , the learning interest variable (X1) have a positive and strong correlation toward the learning achievement variable. It means if the bigger variable score learning interesting (X1) will increase learning achievement (Y) it also toward learning motivation (X2) have a positive correlation to the learning achievement (Y) . The population in this research are 465 students at VII Bintara elementary school Bekasi city 25% x 465 = 116.25, elementary school students at VII Bintara make to become 116 students.Constanta is big as 13.477 said that if no score both variable above togetherness, so every (one) score X variables will increase learning achievement (Y)  as big 1.257 times whereas add one score from X2 variable will increase learning achievement (Y) as big as -0.399 times.            The answer from the respondents as much as 116 students with 24 questioners after counting used statistical product and service solution (SPSS) 16.0 said that if learning interesting (X1) and learning motivation (X2) togetherness  will affect of learning achievement (Y) with regression coeffisien 1.257 X1 + coeffision 0.399 X2 so will be affect to the learning achievement (Y) as big as costanta 13.477.Seen that score F.460.009 > F table (1.92), so Ho is accepted that it means both variables togetherness significant affect the variable toward learning achievement (Y).If faced to these problems and conclusion gotten we suggest the things as below :Needing emphazising to students at VII Bintara elementary school Bekasi city, in order to have learning interest and learning achievement wil be successful.Needing emphazising to all students at VII Bintara elementary school Bekasi city in order to increase the learning motivation so the learning achievement will be successful.Needing emphazising to students at VII Bintara elementary school Bekasi city in carrying out daily learning activity must refer to learning interest and motivation so the learning achievement will be reached.